A Study on The Critical Barriers of The Effectiveness in Building Maintenance for Government School in Batu Pahat, Johor, Malaysia - Syed Burhanuddin Hilmi Syed Mohamad; Muhammad Nur Alif (Journal of Structural Monitoring and Built Environment, 2024)
In Malaysia, responsibility for managing public property, including public schools, is divided among various government departments, and is frequently administered reactively. This will be owing to a lack of clear property goals. The objective for this case study is to center on critical barriers of the effectiveness in building maintenance, to determine the regular practice of building maintenance for public school, to access the classes of the barriers and the potential solution strategic planning for public school. Literature research is required to meet the defined objectives, after which data is collected via questionnaires and analyses. According to research, many of the school buildings lack their own maintenance management procedures, less cost satisfaction, and less experience of managers. Furthermore, as from this case study the critical barrier can be classified to ensure the effectiveness of the building maintenance can be achieve the standard regulation. New strategic of good building management can be made and can focus an action to critical issues that need fast action and cost that need to be spent more specific for those maintenance work only.